Inovasi Produk Lokal untuk Peningkatan Ekonomi Masyarakat melalui Pengembangan Nugget dari Ikan Bandeng - Nurul Hidayat; Febrianingsih. A; Audi Audi; Charla Ta’bi Sulung; Khairunnisa Khairunnisa; Owen Petit; Prithi Arvana Angody; Rabi Simon (Nusantara Mengabdi Kepada Negeri, 2025)
North Kalimantan is one of the provinces in Indonesia that has marine and fisheries potential. The marine and fisheries sector, which has the potential to contribute to the regional economy, is expected to bring about an increase in the economy evenly and evenly in each region. MSMEs have a very important role in driving the wheels of the economy in the North Kalimantan region. The development of Nuggets from Milkfish can be one way to improve the economy of the people of North Kalimantan. This Community Service Activity was carried out in Kampung 4 Village, East Tarakan District, Tarakan City, North Kalimantan Province on May 4, 2025 at 18.30 - 19.30 WITA. This activity was carried out in Taman Berkampung and one of the shops owned by local residents, Kampung 4 Village, attended by MSMEs and visitors/buyers at Taman Berkampung. The methods used in this activity are procedures for managing and improving tropical marine resources, as well as documentation. The benefits of education provided to residents or MSMEs in the area are so that residents can know that utilizing marine resources can increase the competitiveness of local products and encourage economic independence. This activity was carried out through several series, namely making nuggets from milkfish, socialization, nugget testimonials, and documentation